Symptom manifestation of dental local anesthesia with patients who recently received COVID-19 vaccine - Ahmed Abdullah Alaskari; Ebtihal Saad Almutairi; Demah Saleh Midshil Alharthi; Deena Ali Obaid Alqahtani; Atheer Ali Mueedh Alhassan; Roula S Albounni (Wolters Kluwer Medknow Publications, 2022)
Introduction: As a result of Coronavirus Disease (COVID-19) pandemic. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) caused the severe viral pneumonia . Countries have been applying test regulations, vaccination is the top strategy to combat it. Aim: To determine if there was any negative impact of dental local anesthesia on the vital medical condition of patients who recently received the Covid-19 vaccine. Materials and Methods: Before participating in the study, patients had to read and sign a consent form. The following treatments were performed under local anesthesia: ten definitive restorations; two tooth extractions; two scalings and prophylaxis; three root planning; and one root canal treatment. Lidocaine with epinephrine was used on three patients, lidocaine without epinephrine on one patient, and scandicaine2% (mepivacaine hydrochloride) on 13 patients. A questionnaire containing nine specific questions was developed for this study, beginning with a patient's personal information. In the second group, we asked about the symptoms after getting the covid 19 vaccine, and in the third group, we asked about the symptoms after dental work. Results and Discussion: With the limitation of this study, it was evident that there was no correlation between vaccination against Covid-19 and local anesthesia in dental treatment with healthy patients. As the Local anesthetics produce anesthesia by inhibiting nerve ending excitation or by blocking the conduction of peripheral nerves. And COVID-19 vaccine works on the body's immune system. Statistical significance was established at P ≤ 0.05. Conclusion: According to this study, there was no correlation between vaccination against Covid-19 and local anesthesia in dental treatment with healthy patients.